Global lessons from local contexts: The evolution of biomedicine education in Spain - Francisco J. Muñoz; Esther Esteban; Alberto Pérez-Mediavilla; Luis Capitán (PLoS ONE, 2025)
Driven by the presence of faculty with research and clinical backgrounds, and by labor market trends favoring applied training, Biomedicine has emerged as a growing academic field in Spain. This study provides a descriptive analysis of undergraduate Biomedicine programs offered by 18 Spanish universities since 1998, focusing on structural, academic, and outcome-related variables. Data indicate a progressive increase in program availability and student enrollment over the past two decades, reaching a total of 4,614 students in the most recent academic period. Admission criteria remain highly selective, with a mean entry score of 12.5 out of 14. In the absence of guidelines, the curricula from the different universities show a consistent structure, with an emphasis on foundational biomedical sciences in the early academic years – such as Cell Biology, Biochemistry, and Immunology – and the incorporation of advanced subjects in later stages, including Cancer Biology and Bioinformatics. These programs frequently incorporate practical components and research exposure. Over 100 active international collaboration agreements were identified across the institutions studied, reflecting efforts to internationalize their Biomedicine programs. Despite heterogeneity in curricular design, the average graduation rate for the 2022–2023 academic year was 81.8%, and employment outcomes averaged 82.9% over the past decade. The findings suggest a convergence of academic, professional, and institutional factors shaping the development of Biomedicine education in Spain.